Computer methods, imaging and visualization in biomechanics and biomedical engineering selected papers from the 16th International Symposium CMBBE and 4th Conference on Imaging and Visualization, August 14-16, 2019, New York City, USA /: selected papers from the 16th International Symposium CMBBE and 4th Conference on Imaging and Visualization, August 14-16, 2019, New York City, USA. (2020) - Unknown
No abstract available